Effectiveness of Ginger and Lemon Generation on Nau, Vovoging in Trimester I Pregnant Women - Yanti Heryani Salim (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nausea and vomiting in pregnancy if not treated properly can cause other problems, namely Hyperemesis gravidarum. Hyperemesis gravidarum and other complications of Hyperemesis gravidarum can cause birth defects and abortion. Data from the Ciomas Health Center showed that around 60-90% of pregnant women in the first trimester complain of nausea and vomiting every year. The research method used a quasi-experimental design with one group pre-posttest. The sample in this study was 30 pregnant women in the first trimester. The sampling method in this study was non-probability sampling in the form of accidental sampling. The research instrument used a questionnaire. Bivariate analysis used paired t-test. The average frequency of nausea and vomiting in the first trimester of pregnant women before consuming ginger and lemon was 6 times within 24 hours and after consuming ginger and lemon every day for 2 weeks, the average frequency of nausea and vomiting was 3 times within 24 hours. The results of statistical tests showed that giving ginger and lemon juice was effective in reducing the frequency of nausea and vomiting in the first trimester pregnant women with ap value = 0.000.